(untitled) (Bangladesh Journal of Botany, 2023)
Scaly tree ferns (Cyatheaceae) are considered a threatened species due to habitat destruction and over-exploitation. The new data dealing with the diversity and ecology of scaly tree ferns of Mount Salak, Java, Indonesia, are presented. A total of 1387 adult individuals belonging to seven species included in two genera were recorded at the elevation range of 1100-1450 m within an area of 4.5 ha. Alsophila oinops (Hassk.) R.M.Tryon, Alsophila sp., and Sphaeropteris persquamulifera (Alderw.) R.M.Tryon were rare species. Alsophila junghuhniana Kunze and A. polycarpa (Jungh.) R.M.Tryon were found to be abundant in this area. Sphaeropteris glauca (Blume) R.M.Tryon, and S. squamulata (Blume) R.M.Tryon were included as common species. The finding of A. oinops on Mount Salak at 1200-1300 m asl. is a new ecological record for the Malesian region. Some species were found in relatively the same habitat characteristics but differed in their need for light intensity. Scaly tree ferns were found to show varied distribution patterns. Bangladesh J. Bot. 52(3): 741-747, 2023 (September)